Aster Yellows - O'Mara, Judith A.; Bauernfeind, Robert; Stevens, Alan B.; Gast, Karen L. B.; Stevens, Susan (My University, 1993)
This publication is for commercial specialty cut flower production, and concerns a plant disease named aster yellows.
MF1086_1993_08
Keywords: MF1086; Horticulture; Economics; Equipment and Structures; MF